OPTIMIZATION OF MANAGEMENT OF HYPERTENSIVE STATES IN PREGNANT WOMEN WITH THE USE OF INPATIENT MHEALTH REPLACEMENT TECHNOLOGIES - Yusupbaev, R.B.; Muhamedova, Sh.S. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Development and study of the effectiveness of new hospital replacing mHealth technologies in pregnant women with hypertensive disorders. Material and methods: We studied 40 pregnant women with hypertensive syndrome and aggravated obstetric history of hospitalization patients. The studies were conducted in the clinic of RSSPMCOaG and the Ministry of Health of the Republic of Uzbekistan. Patient’s monitor using “TRITON Electronics MPR 6-03” apparatus, “Angioscan” device application. Results: in the 1st group, 40% of women had a full-term birth, in the 2nd - 70%. In the 1st group, preterm labor was observed in 60% of cases, in the 2nd - in 30%, since 2 times less. Operative delivery in the 1st group had to be resorted to in 90% of patients. Conclusions: analysis of the type of waves received on the device “Angioskan”, showed that the type of wave A is one of the markers of contraindications to mHealth, therefore, further examination of pregnant women in stationary conditions is necessary.